FACTORS OF GLOBALIZATION, DEGLOBALIZATION, AND REGLOBALIZATION AT THE PRESENT STAGE (World Economics and Finance Bulletin, 2025)
As John Lennon once said, “Imagine all the people sharing all the world” Some contemporaries considered the words of the classic a utopia, while others saw them as a reflection of the real process of globalization, that is, the consolidation of separate communities into a single whole. Over the past decades, the scientific community's view on globalization has changed repeatedly: sometimes the concept lost popularity (de-globalization), and sometimes it spread its wings again (re-globalization).
Keywords: globalization; repeatedly; contemporaries; popularity